2021
DOI: 10.6061/clinics/2021/e3042
|View full text |Cite
|
Sign up to set email alerts
|

Long–term lung inflammation is reduced by estradiol treatment in brain dead female rats

Abstract: LF, et al. Long-term lung inflammation is reduced by estradiol treatment in brain dead female rats. Clinics (Sao Paulo).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…storm leads to the disruption of endothelial cells and the alveolar barrier (23), and, acute systemic inflammation leads to the infiltration of activated neutrophils to the lungs, leading to tissue injury (28,29). Previous studies from our group have shown that BD increases inflammatory markers in lung tissue in the short and long-term and that E2 presents anti-inflammatory properties that could attenuate lung injury (13,14). The same behavior can be observed in this study after 6h of BD by the increased levels of…”
Section: A B Figure 12mentioning
confidence: 99%
See 1 more Smart Citation
“…storm leads to the disruption of endothelial cells and the alveolar barrier (23), and, acute systemic inflammation leads to the infiltration of activated neutrophils to the lungs, leading to tissue injury (28,29). Previous studies from our group have shown that BD increases inflammatory markers in lung tissue in the short and long-term and that E2 presents anti-inflammatory properties that could attenuate lung injury (13,14). The same behavior can be observed in this study after 6h of BD by the increased levels of…”
Section: A B Figure 12mentioning
confidence: 99%
“…In experimental models, BD in females is followed by the acute reduction of estradiol (E2) and corticosterone with higher inflammation (8). Treatment of donors with either estradiol or corticoids alone has shown positive effects in experimental and clinical studies of BD (9)(10)(11)(12)(13)(14)(15). However, in females, adequate stress response appears to be linked to the presence of both estradiol and corticoids.…”
Section: Introductionmentioning
confidence: 99%